Using Picture Series to Improve Students' Narrative Reading Comprehension at SMK GKPI 2 - Angela Shakila Aurel Pane; Selviana Napitupulu (Young Journal of Social Sciences and Humanities, 2026)
Reading comprehension is a crucial skill in English as a Foreign Language (EFL) learning, particularly for students at the secondary school level. However, many students still experience difficulties in understanding narrative texts due to limited vocabulary, low motivation, and monotonous teaching media. This study aims to improve students’ reading comprehension of narrative texts through the use of Picture Series as an instructional medium. The research employed Classroom Action Research (CAR) with a quantitative approach and was conducted with tenth-grade students of a vocational high school. The research was implemented in two cycles, each consisting of planning, action, observation, and reflection stages. The data were collected through reading comprehension tests and classroom observations. The quantitative data were analyzed using descriptive statistics to determine the mean score and the percentage of students achieving the Minimum Mastery Criteria (KKM ≥ 75). The results showed that students’ reading comprehension improved significantly. In Cycle I, the mean score was 53 with only 6.67% of students achieving the KKM. After improvements were made in Cycle II through more systematic use of Picture Series, the mean score increased to 82, and 83.33% of students achieved the KKM. These findings indicate that Picture Series effectively support students in understanding narrative text structures and sequences of events. Therefore, Picture Series can be recommended as an effective instructional medium for teaching reading comprehension of narrative texts.